The ability of mathematical representation on problem based learning of Krulik and Rudnick strategies - Yulianawati, Dewi Nova; Safa'atullah, Muh. Fajar (Department of Mathematics, Universitas Negeri Semarang, 2020)
In learning mathematics, students still find it difficult to simplify a problem in the form of a problem description into a picture or symbol of mathematics correctly. This relates to students' mathematical representation ability which is still lacking and also its self efficacy. One effort to improve students' mathematical representation ability is through learning through the PBL model of Krulik and Rudnick's strategies. This study aims to examine the classical completeness of students in the aspects of mathematical representation ability, the average mathematical representation ability of students in the learning model Problem Based Learning of Krulik and Rudnick strategies and Problem Based Learning, and describe the ability of mathematical representation of students based on high self-efficacy, moderate, and low. This research uses a mixed method. The research class was taken by simple random sampling. The subjects of this study were 6 students of class VII A of SMP 1 Jambu who were selected by purposive sampling. Data collection using tests, questionnaires, and interviews. The results showed (1) The ability of mathematical representation with the Problem Based Learning model of the Krulik and Rudnick strategies achieving classical learning completeness; (2) The ability of mathematical representation of students in a class that uses Problem Based Learning Krulik and Rudnick strategies is better than the ability of mathematical representation of students in a class that uses Problem Based Learning; (3) Subjects with high self efficacy are able to meet all indicators of mathematical representation ability although there is still a lack of rigor in the work, subjects with moderate self efficacy are sufficiently able to meet the indicators of mathematical representation ability, while with low self efficacy there are still some indicators that have not yet been achieved namely indicators the ability of students to make mathematical equations or models from other given representations and write the steps for solving and solving mathematical problems correctly.